Walking in a cage : Attuning to atmospheric intensities through corporeality - Heimonen, Kirsi (Intellect, 2021)
This article discusses an artistic act: walking for seven sequential days inside a cage made of chicken wire in the grounds of a former mental hospital in Lapinlahti in Helsinki, Finland and its potential to offer insights into past events in mental hospitals through the notions of corporeal attunement and atmosphere. The idea for Walking Cage was prompted by a word in the data, which included memories by patients and non-patients of Finnish mental hospitals gathered in connection with a multidisciplinary research project. Passers-by, occasional co-walkers, weather conditions and the grounds of the former mental hospital partially formed and deformed the atmospheric qualities of the artistic research event. These qualities were experienced through corporeal attuning influenced by the Skinner Releasing Technique, a somatic movement method. The article proposes a singular way of approaching the possibilities of corporeal openness and sensibility in a choreographic process in which, illuminated by, among others, the notions of threshold and limit, one becomes a stranger to oneself by surrendering oneself to atmospheric intensities. This artistic research study adopts a phenomenological approach, drawing mainly on the ideas of Jean-Luc Nancy, Mikel Dufrenne and Emmanuel Levinas.
Keywords: ruumiillisuus; taiteellinen tutkimus; psykiatriset sairaalat